Fatal Adverse Events Associated With Immune Checkpoint Inhibitors in Non–small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Yu, Xiaolin; Zhang, Xiaomei; Yao, Ting; Zhang, Ye; Zhang, Yanxia (Frontiers in Medicine, 2021)
Background: Immune checkpoint inhibitors (ICI) have previously been reported to have a promising potential in terms of the improvement of outcomes in non-small cell lung cancer (NSCLC). Fatal adverse events (FAEs) of ICI are relatively uncommon, and the incidence and risk in NSCLC remain unclear. In the present study, we conducted a systematic review and meta-analysis to evaluate the risk of FAEs in NSCLC patients administered with ICI. Methods: Potentially relevant studies were identified in PubMed, Embase and Cochrane library database from inception to September 16, 2020. The systematic review and meta-analysis included randomized controlled trials (RCT) that reported treatment-related FAEs in NSCLC.The pooled incidence and risk ratios (RR) were calculated to evaluate prospective risk. Results: Twenty clinical trials that included a total of 13483 patients were selected for the meta-analysis. The overall incidence of FAEs was 0.65% (95% CI: 0.31-1.07, I2 = 50.2%) in ICI monotherapy, 1.17% (95% CI: 0.74-1.69, I2 = 56.3%) in chemotherapy, and 2.01% (95% CI: 1.42-2.69, I2 = 5.9%) in the combination therapy (ICI and chemotherapy). ICI monotherapy was associated with lower incidence of FAEs caused by blood system disorders (RR = 0.23, 95% CI: 0.07-0.73, P = 0.013, I2 = 0%) and infectious diseases (RR = 0.29, 95% CI: 0.13-0.63, P = 0.002, I2 = 0%). The incidence of pneumonitis significantly increased in immunotherapy (RR = 5.72, 95% CI: 1.14-28.80, P = 0.03, I2 = 0%). Conclusions: The results of the present study demonstrate that ICI monotherapy decreases the risk of FAEs ,while the combined regimens with chemotherapy have the opposite tendency as compared to conventional chemotherapy. While the patients who received chemotherapy suffered the risks of death mainly from myelosuppression and infection, those who received immunotherapy were mainly threatened by immune-related pneumonitis.